2014
DOI: 10.15407/ubj86.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Functions of tocopherols in the cells of plants and other photosynthetic organisms

Abstract: Tocopherol synthesis has only been observed in photosynthetic organisms (plants, algae and some cyanobacteria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…OHP1 and OHP2 expression was additionally co-regulated with genes of the IPP metabolism, which is the starting point for isoprenoid biosynthesis (Vranová et al, 2013). Among the isoprenoids, especially the terpenoids like phytols, tocopherols and carotenoids are essential for assembly and functionality of photosynthetic pigment-protein complexes as well as for photoprotection (Domonkos et al, 2013; Mokrosnop, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…OHP1 and OHP2 expression was additionally co-regulated with genes of the IPP metabolism, which is the starting point for isoprenoid biosynthesis (Vranová et al, 2013). Among the isoprenoids, especially the terpenoids like phytols, tocopherols and carotenoids are essential for assembly and functionality of photosynthetic pigment-protein complexes as well as for photoprotection (Domonkos et al, 2013; Mokrosnop, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…This finding shows a positive role for α‐tocopherol in the membrane stability of SUVs carrying DHA and EPA. The findings of Mokrosnop () showed that the incorporation of α‐tocopherol in the formulation can improve the strength of the membrane, increase its hydrophilic quality and decrease its permeability, thereby increasing loading.…”
Section: Resultsmentioning
confidence: 99%
“…The mixed tocopherols are found in several plants and has antioxidant activity. [30] Therefore, it is impossible to relate the antimicrobial activity only to the presence of tocopherol, and it would be necessary to test alpha, beta, gamma, and delta-tocopherol individually. [31] Especially, because Green et al [32] reported a significant delivery of Vitamin E acetate to the surface of the gingival tissues from the test toothpaste (mean level = 50.7 ppm) compared to a control dentifrice (=1.4 ppm) and Scott et al [33] showed that buccal and gingival epitheliums are able to metabolize Vitamin E acetate, to the free form, Vitamin E.…”
Section: Discussionmentioning
confidence: 99%